한우의 FABP4 유전자 선별에서 사육환경 보정 효과 - 김현지; Hyun Ji Kim; 이제영; Jea Young Lee (Ŭngyong tʻonggye yŏnʼgu, 2015)
가축의 경제적인 특성은 환경적인 요인과 유전적인 요인의 영향을 복합적으로 받는다. 우리는 한우의 경제적 특성에 영향을 미치는 유전적인 요인에 관심이 있으며, 우리의 목적은 경제형질에서 환경적인 요인을 보정하여 유전효과를 더욱 정확하게 검증하는 것이다. 본 연구에서는 환경적인 요인과 유전적인 요인으로 구성된 통계모형을 구축하고, 이 모형에서 환경적인 요인인 사육농가의 효과와 도축일령의 효과를 제거하여 보정된 경제형질값을 구한다. 그리고 보정 전·후 경제형질값을 다중인자차원축소 방법에 적용하여 각각의 우수 유전자와 유전자조합을 선별하고, 정확도를 비교한다. 그 결과, 우리는 환경요인을 보정한 경제형질값을 활용하여 우수 유전자 선별의 정확도를 높였고, 한우의 등급과 지방산과 깊은 연관이 있는 우수한 FABP4 유전자를 선별하였다. Economic-traits of livestock are affected by environmental and genetic factors. We are interested in genetic factors that influence the economic-traits of Korean cattle. It is necessary to adjust environmental factors in order to enhance the accuracy of the genetic effect analysis. In this paper, we propose a statistical model of Korean cattle that exclude environmental breeding farm and age factors. We formulated an adjusted economic-trait value, and applied multifactor dimensionality reduction (MDR) method to data of beforeand-after adjustment to identify major FABP4 genes. We were able to increase the accuracy of the analysis after adjustment and identify superior FABP4 genes that influence grade and fatty acid.